Effects of Wii Fit Balance Training on Confidence Level & Quality of Life of Subjects of Type 2 Diabetes Mellitus with Neuropathy - Kiran Khushnood Nasir Sultan, Riafat Mehmood (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2018)
Objective: To determine the effects of Wii fit balance training on confidence level during several daily activities and quality of life of individuals of type 2 diabetes mellitus with neuropathy. Methods: This experimental study was carried out at physical therapy department of Kulsurn International Hospital, Islamabad from July to December 2017, on 67 type 2 diabetic subjects who fulfilled the inclusion criteria after taking verbal and written consent. Baseline assessment was done and subjects were provided with 30 minutes Wii Fit gaming twice a week for 12 weeks. After completion of 12 weeks, reassessment was done and data was analyzed by SPSS version 21.0. Six participants were dropped. Berg balance scale (BBS), activity balance confidence (ABC) and Euro 5D 5L were used as outcome measures. Results: Total 61 subjects were analyzed at the completion of 12 weeks. There were 45 males and 16 females. BBS has improved from 43.33+2.67 to 47.17±2.51, ABC 85.21±5.10 to 87.49±3.74 with significance of <0.001. Mobility level changed from 2.63±0.70 to 1.57±0.64, self-care 2.06±0.65 to 1,31±0,46, usual activities 2.29±0.61 to 1.29+0.45. pain/discomfort 1.93±0.57 to 1.32±0.47, anxiety/depression 2.04±0.56 to 1.34±0.47 while health status improved from 75.98±6.04 to 84.34±6.22 with significance <0,001. Conclusion: Wii Fit balance training improves confidence level while performing several activities and quality of life of subjects with type 2 diabetes.